¬¬¬ PEER ATTACHMENT AND ONLINE NETWORKING TO ENHANCE EMOTIONAL WELLBEING DURING COVID19 PANDEMIC AMONG ADOLESCENTS: LITERATURE REVIEw - AZADEH MOOUSAVI (Study Program Guidance and Counseling, Univesitas Pendidik, 2022)
: Nowadays the issue of emotional intelligence is catching most of the attention in both academic and non-academic areas especially during covid19 pandemic. Researchers and parents are seeking a way to enhance adolescent’s emotional intelligence. Improve emotional intelligence is like a pathway to increase mental health and wellbeing. Environmental impulses such as communication with peers if in real life and in the case of online networking by the satisfying a sense of belonging are key factors to improve emotional intelligence. Today, the internet has become a vital factor in all aspects of people's lifestyle and networking has become more popular among adolescents to organize their contacts by giving and receiving feedback and enhance and facilitate community during covid19 lockdown. In this regard in this article is tried to focus more on the role of Facebook to enhance emotional wellbeing during Covid19 pandemic.